Capacitive behavior of activated carbons obtained from coffee husk. Issue 62 (15th October 2020) - Ramirez, Nathalia; Sardella, Fabiana; Deiana, Cristina; Schlosser, Anja; Müller, Dennis; Kißling, Patrick A.; Klepzig, Lars F.; Bigall, Nadja C.
Abstract : This paper analyzes the electrochemical and physicochemical properties of activated carbons developed from coffee husk through different activation routes. Abstract : Sustainable agroindustry has presented many challenges related to waste management. Most of its residues are lignocellulosic biomass materials with great application potential due to their chemical composition, hence the use of biomass-derived carbon materials in energy storage has received growing interest in recent years. In this work, highly micro-porous carbonaceous materials using the endocarp of the coffee fruit or coffee husk (CH) as precursor are obtained. Specifically, three different activating agents (KOH, K2 CO3, and steam) to derive activated carbons (ACs) with good capacitive properties are tested. The properties of ACs such as surface chemistry, texture, crystal graphite size, and order in the carbonaceous structure are assessed and compared. The capacitive behavior inherent to the activation routes is also characterized by means of Cyclic Voltammetry (CV), Galvanostatic Charge/Discharge (GCD) and Electrochemical Impedance Spectroscopy (EIS). The obtained specific capacitance values range from 106 to 138 F g −1 for a discharge current of 0.5 A g −1 . These results nominate coffee husk as a good precursor of carbonaceous materials suitable for energy storage.